"The Offspring of Drunkards": Gender, Welfare, and the Eugenic Politics of Birth Control and Alcohol Reform in the United States. Issue 3 (2021) - Thompson, Lauren MacIvor
Abstract: The social politics of women's alcohol use is controversial given current debates over maternal-fetal health, fetal alcohol syndrome, and debates about welfare. Exploring the early twentieth century intersections of Prohibition, birth control reform, and alcohol politics reveals the historical roots of current recommendations surrounding women, alcohol, and public assistance.